2023
DOI: 10.3390/vaccines11020415
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Transplacental Antibody Transfer in Pregnant Women Immunized with Different SARS-CoV-2 Homologous or Heterologous Schemes

Abstract: There is scarce information related to transplacental antibody transfer against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) with different homologous and heterologous vaccination schemes. This study aimed to correlate the magnitude of transplacental transfer anti-SARS-CoV-2 antibodies in different homologous and heterologous schemes. An observational cross-sectional study was developed to identify pregnant women vaccinated against SARS-CoV-2. They were questioned about their immunization statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Other studies, including our own previously published research, have demonstrated the importance of transplacental neutralizing antibody (Nab) transmission from mothers vaccinated against COVID-19, or other diseases such as influenza, to their babies [ 7 , 8 , 9 , 10 , 11 , 12 ]. Our previous data demonstrated cord-to-maternal Nab inhibition rate ratios of 0.99 and 0.90 for SARS-CoV-2 wildtype and Delta variants (B.1.617.2) following receipt of two doses of COVID-19 vaccine, respectively [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, including our own previously published research, have demonstrated the importance of transplacental neutralizing antibody (Nab) transmission from mothers vaccinated against COVID-19, or other diseases such as influenza, to their babies [ 7 , 8 , 9 , 10 , 11 , 12 ]. Our previous data demonstrated cord-to-maternal Nab inhibition rate ratios of 0.99 and 0.90 for SARS-CoV-2 wildtype and Delta variants (B.1.617.2) following receipt of two doses of COVID-19 vaccine, respectively [ 12 ].…”
Section: Introductionmentioning
confidence: 99%